Effect of Gladiolus psittascinus Hook bulb supplemented diet on nootropic-related biomolecules in scopolamine-induced cognitive dysfunction rats - Folake L. Oyetayo; Seun F. Akomolafe; Adegboyega D. Ogunlade (Elsevier, 2023)
Background: Gladiolus psittascinus (G. psittascinus) Hook, commonly known as maid of the mist, is an herbaceous and bulbous plant used frequently in folk medicine to treat mental illnesses; without any clear-cut explanations for its mode of action. Purpose: This investigation examined the impact of a G. psittascinus Hook bulb supplemented diet (GP) on scopolamine-induced cognitive dysfunction and reformed neurochemicals linked to Alzheimer's disease (AD) in rat cerebral cortex and hippocampus. Study design: Rats were fed GP (5 and 10%) for 14 days, and on the final day, 2 mg/kg of scopolamine was administered intraperitoneally. Methods: The Y-maze and Morris water Maze tests were used to evaluate cognitive function. Acetylcholinesterase (AChE), butyrylcholinesterase (BChE), Na+/K+ ATPase, adenosine deaminase (ADA) and monoamine oxidase (MAO) activities in the hippocampus and cerebral cortex of rats were determined. Furthermore, neurotransmitter, gamma-aminobutyric acid and oxidative stress markers were also assessed. G. psittascinus Hook bulb was characterized using HPLC-UV/visible spectroscopy. Results: In rats treated with scopolamine, GP enhanced cognitive function by raising the memory index. Rats administered scopolamine showed increased AChE, BChE, ADA, MAO, and decreased the activity of Na+/K+ ATPase in the cerebral cortex and hippocampus. However, following administration of GP, the activities of these enzymes drastically decreased while Na+/K+ ATPase activity increased. Gamma-aminobutyric acid concentration significantly increased after treatment with GP, this also ameliorated antioxidant status impairment in scopolamine treated rats. Beta-sitosterol, daucosterol, nicotiflorin, tamarixetin-3-robinobioside, quercetin, kaempferol and isopentyl-gentiobioside were identified in G. psittascinus Hook bulb. Conclusion: The capability of the G. psittascinus bulb to enhance cognition, neurotransmitter, and mitigate cholinergic enzymes dysfunction, ADA, MAO, Na+/K ATPase activities, and neuronal antioxidant status in scopolamine-induced cognitive dysfunction rats may help to support the possibility of neuroprotection conferred by G. psittascinus bulb and also explains the potential mechanisms of action of the bulb as discovered in folklore